Fish waste as an alternative resource for gulls along the Patagonian coast: availability, use, and potential consequences - Yorio, Pablo Martin (2004)
We evaluated the volumes of waste from fish processing plants in Chubut Province, Argentina, and discuss its potential consequences for Kelp Gull (Larus dominicanus) population dynamics and coastal management. Mean volume of waste produced between 1989 and 2001 in three coastal cities was 49.8± 10.9 thousand tonsy -1. The amount of waste varied between years and cities, being larger at Puerto Madryn and Comodoro Rivadavia than at Rawson (24.1, 19.3 and 6.4 thousand tons y -1, respectively). Waste was disposed at the three cities during all months of the sampled years. Large numbers of Kelp Gulls have been recorded taking advantage of fish waste disposed at these waste sites throughout the year. Considering its energetic content, waste generated at processing plants may support a population of between 101000 and 209000 Kelp Gulls. Fish waste could be contributing to their population expansion through increased survival and breeding success. Conflicts due to the use of waste and derived effects on other coastal species and human populations could be minimized by adequate fish waste management.